2018
DOI: 10.1021/acs.nanolett.8b02806
|View full text |Cite
|
Sign up to set email alerts
|

Patterning-Induced Ferromagnetism of Fe3GeTe2 van der Waals Materials beyond Room Temperature

Abstract: Magnetic van der Waals (vdW) materials have emerged as promising candidates for spintronics applications, especially after the recent discovery of intrinsic ferromagnetism in monolayer vdW materials. There has been a critical need for tunable ferromagnetic vdW materials beyond room temperature. Here, we report a real-space imaging study of itinerant ferromagnet FeGeTe and the enhancement of its Curie temperature well above ambient temperature. We find that the magnetic long-range order in FeGeTe is characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
183
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(198 citation statements)
references
References 43 publications
14
183
1
Order By: Relevance
“…Nevertheless, thin films of Cr 2 Ge 2 Te 6 , Fe 3 GeTe 2 , and FePS 3 for example show intrinsic ferromagnetism or antiferromagnetism, which leads to good prospects in spintronic device applications. [2a], The high Curie temperature of 220 K and strong anisotropy of the magnetic state favors Fe 3 GeTe 2 over other ferromagnetic van der Waals materials . The hexagonal structure of Fe 3 GeTe 2 contains metal atom substructures sandwiched by tellurium layers building the van der Waals gap …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, thin films of Cr 2 Ge 2 Te 6 , Fe 3 GeTe 2 , and FePS 3 for example show intrinsic ferromagnetism or antiferromagnetism, which leads to good prospects in spintronic device applications. [2a], The high Curie temperature of 220 K and strong anisotropy of the magnetic state favors Fe 3 GeTe 2 over other ferromagnetic van der Waals materials . The hexagonal structure of Fe 3 GeTe 2 contains metal atom substructures sandwiched by tellurium layers building the van der Waals gap …”
Section: Introductionmentioning
confidence: 99%
“…A, Crystal structure of Fe 3 GeTe 2 (FGT) . B, Polar RMCD signal for a monolayer FGT at several fixed temperatures .…”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 99%
“…The typical Curie temperatures of 2D‐vdW magnets are much lower than room temperature, and this figure of merit is largely limited by exchange interaction and magnetic anisotropy, according to the Mermin‐Wagner theorem. The group of Qiu et al has demonstrated an increase in the Curie temperature associated with FGT flakes by magnetic domain engineering . Figure D displays the magnetic domain images for unpatterned, micro‐sized diamond‐shaped and rectangular patterned structures at 300 K. Unlike the unpatterned FGT flakes with a single domain configuration, the in‐plane magnetization component within the patterned FGT microstructures not only remains but also develops into a magnetic vortex state in the diamond‐shaped microstructures and a magnetic domain state in the rectangular structure, respectively.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations